Eksplorasi Budaya Kontemporer di Indonesia - Khisbulloh, Afan (Maliki Interdisciplinary Journal, 2025)
This study aims to describe the dynamics of contemporary culture in Indonesia, focusing on the interaction between tradition and modernity. Through descriptive methods, this study explores various cultural elements, such as art, music, cuisine, and local traditions, as well as the significant influence of globalization. Data were obtained through field observations, interviews with artists, and document analysis.The results show that although Indonesia is rich in tradition and cultural diversity, the phenomena of modernity and globalization have brought significant changes. For example, many artists combine traditional elements with contemporary styles, creating works that are unique and relevant to the times. In addition, the emergence of social media has accelerated the spread of culture, allowing the exchange of ideas and collaboration between artists from various regions. However, challenges are also faced, such as the decline in interest of the younger generation in traditional culture and concerns about cultural homogenization. This study concludes that it is important to maintain a balance between preserving culture and adapting to changing times. Therefore, collaborative efforts between the government, society, and artists are needed to develop and preserve Indonesian culture.